Transvestites: bodies in transit? Dreams, myth and reality - Maria Alves de Toledo Bruns; Edmar Henrique Dairell Davi (Universidade Estadual Paulista Júlio de Mesquita Filho, 2016)
The goal of this article is to discuss the phenomenon of the ethos of affective sexual experience of transvestites at the interface with modeling one's body. A changing reality, the body in contemporary society is a kind of merchandise - a product entitled to minor repairs and predetermined duration. It was also observed the construction of identities and subjectivities based on artifacts established under or on the skin: piercings, tattoos, scarification, silicone, hormones, body building, crossdressing - which have turned the body into a means of affirmation of the self. The use of silicone, hormones and plastic surgery to achieve the ideal body modeling by transvestites has become commonplace among this population leading to an issue of public health due to the injuries, deformities and even death that often result from such practices. The phenomenological method was chosen to analyze, understand and interpret the speeches of three transvestites belonging to social classes C and D; aged between 20 and 30 years on the meanings they attribute to the process of modeling their body and the affective sexual practices arising from such transformation. The results obtained from the analysis of the three interviews led to three categories: "The dream of beauty and a perfect body"; "Pain and the recovery process as a rite of passage"; and "Change in behavior / personality resulting from the applications". In their search of the perfect body they dare and cross the ethical boundaries of aesthetics and health. They subvert the sense of self-care to meet the market logic. The transvestites mutilate and shape their bodies; they shape a sui generis body that seeks balance between the feminine and the masculine and also claims the existence of a particular ethos.